PERTUMBUHAN BIBIT KOPI BERDASARKAN TINGKAT KEMATANGAN BUAH DAN APLIKASI CENDAWAN ENDOFIT - I Irma; S Syamsia; Abubakar Idhan; Amanda Patappari Firmansyah (Fapetrik-UMPAR, 2022)
One of the efforts to accelerate the seeds' dormancy period is to use physiologically mature seeds and applicant of endophytic fungi. This study aims to determine the level of fruit maturity and the type of fungus that can accelerate germination and growth. This research was arranged with a Randomized Block Design with 2 treatments, namely the level of fruit maturity (based on the color) and the type of endophytic fungus. The maturity level of coffee cherries (coffee fruit skin color) consists of 4 levels, namely: brown, red, orange, and yellow. The second factor is the type of endophytic fungus with 2 levels, namely: isolate CE-1, isolate CE-5, and as control without endophytic fungi. The parameters observed were the percentage of germination (%), cotyledon rupture (days), fully open Institute leaves (days), the emergence of the first leaf (days), seedling height (cm), number of leaves (strands), root length (cm), weight plant fresh weight (gr), root fresh weight (gr), leaf root weight (gr), plant dry weight (gr), root dry weight (gr), leaf dry weight (gr). The results showed that the maturity level of coffee cherries significantly affected the percentage of germination, emergence of the first leaves, and plant fresh weight. The best fruit maturity level for the percentage of germination was red with 98.5% germination percentage, first leaf appearance (44 days), and plant fresh weight (0.25 g). The type of endophytic fungus isolate had a significant effect on the percentage of germination, fully open Institute leaves, and the emergence of the first leaves. The endophytic fungus CE-5 showed the best results in the percentage of germination parameters (93.06%), fully open institutional leaves (28 days), and first leaf emergence (46 days). The use of red coffee cherries with the application of endophytic fungi can be used to germinate and growth of coffee seedlings.